1988
DOI: 10.1073/pnas.85.12.4232
|View full text |Cite
|
Sign up to set email alerts
|

Potential positive and negative autoregulation of p60c-src by intermolecular autophosphorylation.

Abstract: The product of the protooncogene c-src is a protein-tyrosine kinase, p0C-src, that is normally inhibited by phosphorylation at a tyrosine residue close to the C terminus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 40 publications
8
139
2
Order By: Relevance
“…Moreover, 8-azido-ATP failed to induce crosslinking, establishing that the Q-phosphate-azido substitution was critical (data not shown). Since Csk can phosphorylate Src and Src can autophosphorylate intermolecularly [8,9], it should be possible to observe a variety of crosslinked adducts, consistent with the heterogeneous pattern observed in Fig. 4.…”
Section: Protein Crosslinking By Compoundsupporting
confidence: 72%
“…Moreover, 8-azido-ATP failed to induce crosslinking, establishing that the Q-phosphate-azido substitution was critical (data not shown). Since Csk can phosphorylate Src and Src can autophosphorylate intermolecularly [8,9], it should be possible to observe a variety of crosslinked adducts, consistent with the heterogeneous pattern observed in Fig. 4.…”
Section: Protein Crosslinking By Compoundsupporting
confidence: 72%
“…Our results agree with data presented by others who showed that the Src tyrosine kinase retains activity when phosphorylated on Tyr-416 and Tyr-527 (41). 3 Previous work in our laboratory as well as kinetic data by other groups suggest that the activating phosphorylation of Tyr-394 in Src family members is an intermolecular event rather than intramolecular reaction (22,(42)(43)(44). 4 Intermolecular phosphorylation of Tyr-394 may be carried out by Lck in vivo, but it is quite possible that other Src family members, or non-Src tyrosine kinases, may also act to phosphorylate Tyr-394 and activate Lck.…”
Section: Discussionmentioning
confidence: 97%
“…Normally, inactive c-Src exists as a tight complex in which the SH2 domain interacts with phosphotyrosine at position 527 localized in the C-terminal region of the protein. Src activation results in the displacement of C termini from the SH2 domain proteins, promoting interactions with SH2 and/or SH3 ligands that prime c-Src for activation and thereby allowing phosphorylation of the kinase on Tyr 416 (26,27).…”
Section: Discussionmentioning
confidence: 99%